A typological Study of the Historical Mosques in Erbil City - Mustafa, Faris A.; Ismael, Zhiman Kh. (Sulaimani Journal for Engineering Sciences, 2019)
A mosque is a place of worship for Muslims. Erbil city contains a collection of historical mosques built in different eras dating back to 900 years ago. This paper highlights the plan typology of mosques and compares them with the known Islamic architectural typologies in an attempt to fill this gap of knowledge on such topics, especially with regard to the built environment of historic mosques in the city of Erbil. The central question of the research was: is the type of plans of the historical mosques in Erbil city related to a specific style in Islamic architecture? The aim of the research is to study the plan layout typology of mosques and to identify to which extent these typologies connected with Islamic known styles. The methodology is offering the known Islamic styles around the world with examples, selecting 5 historical mosques for analyzing their plan morphologies graphically according to (shape of the prayer hall, corridor, and courtyard) then comparing these plans with the plans of Islamic styles. From the analysis, a typological tendency in the historical mosques of Erbil city was recognized. The discussion in this paper emphasizes the correlation between the typology of historical mosques in Erbil city with the known Islamic architectural typologies of mosques. As a result, the architectural typologies of the floor plan of historical mosques in Erbil city were identified. The study concluded several types of plans, such as Ottoman style, Umayyad style, and irregular plan style. The current research revealed that the typology of plans in historical mosques in Erbil city related to the plan typology of Islamic known styles.
Keywords: Typology; Historical mosque; Islamic architecture; Plan; Erbil city